Social Assistance Strategy for the Family Hope Program (PKH) in Improving the Independence of Beneficiary Families in the Cempaka Putih Village Area South Tangerang - Zen, Muhammad Hilmy; Muhtadi, Muhtadi (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
Social assistance is a strategy in Program Keluarga Harapan (PKH) which of course aims to improve the quality of Beneficiary Families (KPM) of PKH assistance. Social assistance is also an evaluation material for the government to continue to empower its people. This study aims to determine the process and results of the social assistance strategy ofProgram Keluarga Harapan (PKH) in the Cempaka Putih Village, South Tangerang. This study uses a descriptive qualitative method. Data collection methods are observation, interviews, and documentation. The data sources used are primary data and secondary data. The informant selection technique uses the snowball sampling technique. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validity technique uses source triangulation. The results of the study showed that the independence of Beneficiary Families (KPM) has increased, but not too significantly with evidence that not all KPM can utilize the support program properly and regularly. In addition, there are still many KPM who depend on PKH assistance in the Cempaka Putih Village, South Tangerang.